2017
DOI: 10.9734/ajaees/2017/33503
|View full text |Cite
|
Sign up to set email alerts
|

Farmer’s Level Motivation on Sunflower Cultivation in a Rice Based Cropping Pattern of Patuakhali District

Abstract: The aim of the study was mainly to determine and describe the extent of the motivation on sunflower cultivation and also explore relationship between the 12 selected characteristics of the farmers with motivation on sunflower cultivation. The study was designed with mixed method approach where, both qualitative and quantitative analyses are blended in a rational way to have a deeper understanding about research problems. The study was conducted in Dumki and Patuakhali Sadar Upazilla of Patuakhali district, Ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…In coastal districts of Bangladesh, farmers' access to training and extension media were found to be highly related to the yield gap of Aman rice (Roy et al, 2019). These previous studies all support our findings (Rana et al, 2017;Adebayo and Oladele, 2013;Razeim et al, 2017;Badhan et al, 2017).…”
Section: Relationship Between Socio-demographic Features and Farmers'...supporting
confidence: 86%
See 2 more Smart Citations
“…In coastal districts of Bangladesh, farmers' access to training and extension media were found to be highly related to the yield gap of Aman rice (Roy et al, 2019). These previous studies all support our findings (Rana et al, 2017;Adebayo and Oladele, 2013;Razeim et al, 2017;Badhan et al, 2017).…”
Section: Relationship Between Socio-demographic Features and Farmers'...supporting
confidence: 86%
“…They are willing to accept a high level of risk in farming, even when a new technology proves futile. Badhan et al (2017) found similar findings.…”
Section: Factors Associated With Farmers' Attitudes Towards Yield Gap...supporting
confidence: 69%
See 1 more Smart Citation
“…The average cabbage farmers had experience in farming because the average cabbage farmers were old and had been involved in cabbage farming for a long time. A different result was revealed by [8], showing that most of the farmers' experience was in the low category, which was 2-12 years Because these farmers only succeeded their parents, so they only got their experience by learning from their parents' experiences.…”
Section: Relatedness Needsmentioning
confidence: 87%
“…In solving their farming problems, they used the same solution as the first time they attempted because they have lack of training. A study from [8] revealed that training has a lot of contribution for farmers to carry out their farming because training helps farmers understand and determine the applications to be used and provides useful farming information.…”
Section: Relatedness Needsmentioning
confidence: 99%